Quantum Computing: Potential Impacts on Cryptography and Data Security - Ojha, Dharma Raj (Journal of Durgalaxmi, 2024)
Quantum computing introduces a new paradigm that brings about, by its very nature, revolutionary changes in cryptography and data security. This section will shortly discuss some of the impacts of quantum computing technologies on cryptographic protocols, focusing on the various vulnerabilities introduced by algorithms such as Shor's algorithm, capable of solving some problems-integer factorization and discrete logarithms-provided that polynomial complexity is achieved on quantum computers. Quantum algorithms will soon render traditional cryptographic techniques using RSA and ECC vulnerable, hence the development need for PQC techniques. It purports to analyze the available research and discusses the development, challenges, and future directions of quantum- resistant cryptographic methodologies. This paper emphasizes that transitioning towards PQC is urgent to maintain all attributes of data, such as confidentiality, integrity, and authentication in the quantum computing era. QKD emerges as a promising approach that uses the principles of quantum mechanics to provide physical-layer security for communication channels. Based on these phases, the paper develops into recommendations on building resilience in cryptography with the prospect of quantum computing.